"Always do your best!"—The relationship between food addiction, exercise dependence, and perfectionism in amateur athletes - Hauck, C.; Schipfer, M.; Ellrott, T.; Cook, B. (German Journal of Exercise and Sport Research, 2020)
Food addiction is discussed as a substance-related addictive disorder, which is prevalent in normal and underweight subjects. Addictions often co-occur. It was suggested that food addiction and exercise dependence (behavioral addiction), may co-occur in vulnerable athletes. This assumption was made since the eating behavior of athletes in certain situations is similar to the eating behavior seen in food addiction. In addition, exercise dependence may play a significant role in individuals` eating related pathologies, and thus possibly also in food addiction. Athletes may be an interesting population to examine the co-occurrence of food and exercise addictions, as athletes represent a group that is potentially at-risk for both, eating problems and exercise dependence. Perfectionism is a construct that has been implicated in both, exercise dependence and eating disorders. Current study explores potential relationships among the two addictive disorders food addiction and exercise dependence—with perfectionism being the common thread between the two. Method: A total of 1022 German speaking amateur athletes completed an online questionnaire consisting of the questionnaires Yale Food Addiction Scale 2.0, Questionnaire to diagnose exercise-dependence in endurance sports and Multidimensional inventory of perfectionism in sport. Result: A mediator effect of exercise dependence on the relationship between perfectionism and food addiction was found. Approximately 4 % (positive)/6 % (negative) of the variance in food addiction were accounted for by the mediator. Conclusion: The appearance of food addiction in normal/underweight individuals may partially be explained by sports-related reasons, e.g. exercise dependence and perfectionism. Zusammenfassung Hintergrund: Das Konstrukt der `food addiction` postuliert einen Zusammenhang zwischen Nahrungsaufnahme und Sucht. `Food addiction` findet sich unter anderem bei Personen mit Normal- und Untergewicht. Suchterkrankungen treten häufig gemeinsam auf. Es wurde vermutet, dass `food addiction` und Sportsucht (Verhaltenssucht) bei vulnerablen Athleten gemeinsam auftreten könnten. Diese Vermutung resultierte daraus, dass das Essverhalten bei Athleten in bestimmten Situationen dem suchtartigen Essverhalten bei `food addiction` ähnlich ist. Zudem spielt Sportsucht eine bedeutsame Rolle bei individuellen Ess-Pathologien, und damit auch bei `food addiction`. Athleten stellen eine gute Studienpopulation zur Untersuchung der Kookkurrenz von `food addiction` und Sportsucht dar, da bei Athleten sowohl das Risiko für Essstörungen, als auch für Sportsucht erhöht ist. Perfektionismus ist ein Konstrukt, das an Essstörungen und Sportsucht beteiligt ist. Die vorliegende Studie untersucht mögliche Zusammenhänge zwischen `food addiction` und Sportsucht, und erfasst dabei zudem Perfektionismus, als gemeinsames Merkmal der beiden Störungsbilder. Methodik: An der Studie nahmen 1022 deutschsprachige Amateurathleten teil. Sie füllten einen Onlinefragbogen mit den drei Fragebögen Yale Food Addiction Scale 2.0, Fragebogen zur Erfassung des Sportverhaltens von Ausdauersportlern und Mehrdimensionales Inventar zu Perfektionismus im Sport aus. Ergebnis: Es wurde ein Mediatoreffekt von Sportsucht auf den Zusammenhang zwischen Perfektionismus und `food addiction` gefunden. Rund 4 % (positiver Perfektionismus)/6 % (negativer Perfektionismus) der Varianz von `food addiction` konnten durch den Mediator erklärt werden. Schlussfolgerung: Das Auftreten von `food addiction` bei normal-/untergewichtigen Individuen könnte teilweise durch sportbedingte Gründe, wie Sportsucht und Perfektionismus, erklärt werden.